„Thomas Mann – langweilig und ohne dramaturgische Spannung“. Deutschsprachige Literatur in Nikodem Cieszyńskis Zeitschrift Roczniki Katolickie - Jakubów, Marek (Studia Germanica Posnaniensia, 2019)
The periodical Roczniki Katolickie, published in the 1920s and 1930s, was part of an anti-modernist project created in European Catholic circles. The information about German literature, which can be found in the magazine, on the one hand, served as a means of reinforcing feelings of belonging to a borderless confessional community and, on the other hand, constituted an element of German-Polish cultural transfer. Analyzing its content helps determine the extent of influence of the forms and aesthetic and literary categories disseminated within the Catholic milieu as well as the transformations of the image of the stereotypical German that was dominant in Poland at that time.